Violence against women in the production of the Inter-American comission and the Inter-American court of human rights La violencia contra las mujeres en las producciones de la comisión y la corte interamericana de derechos humanos - Clérico, Laura; Novelli, Celeste (ESTUD CONST, 2014)
This article aims to identify and analyze the legal standards built by the Inter-American Commission and Inter-American Court of Human Rights on the following topics: the definition of violence against women/gender violence; the legal description of the actions or omissions that constitute a breach to human rights and which are also an expression of gender inequality; obligations and appropriate means of reparations owed by States to eradicate gender violence. The analysis finds progress on gender mainstreaming in the productions of the Inter American System of Human Rights, but also a narrow conception of violence against women focused mainly on sexual violence. This approach leaves out many other important aspects. Furthermore, this paper warns about the emphasis on access to justice as a reparatory measure that difficult to consider the implementation of other adequate actions towards the eradication of violence against women.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Access to Justice; Inter American Commission; Inter American Court; Inter American System of Human Rights; Violence against women